Deficit Limits, Budget Rules, and Fiscal Policy - Manasse, Paolo (IMF Working Papers; Working Paper ;, 2005)
The paper presents a simple model for discussing the effects of deficit limits and budget rules on fiscal policy. I find that limits on deficit-output ratios provide incentives to implement procyclical policies when the economy is in intermediate states, and countercyclical policies only in very "good" and very "bad" economic times. As a result, fiscal "reaction functions" are not monotonically related to the state of the economy. Deficit limits are found to exert discipline only provided the limit is tight and the expected sanction large, albeit at a relatively large welfare cost. Moreover, when fiscal choices are made under a veil of ignorance about the output gap, an increase in volatility is likely to raise the level of the budget deficit. Finally, concerning the design of fiscal frameworks, when excessive deficits arise from a political bias, deficit limits should be symmetric and not state-contingent.